فاعلية استخدام إستراتيجية التعلم النشط في تدريس التمرينات الرياضية لتلاميذ مرحلة الأساس بولاية الخرطوم - د. عبد الرحمن محمد احمد عباس; ا حليمة إبراهيم إسحاق احمد (White Nile Journal for Studies and Research, 2020)
The study aimed to identify the effectiveness of using the active learning strategy to teach the exercise subject at the basic stage in Khartoum state. The study consisted of 40 students distributed randomly into two groups of 20 students per group. The experimental group was studied using the active learning strategy and the control group was studied in the traditional way, and the two researchers used The experimental approach, and the statistical program Spss was used to process the data, and the study showed the following results: There are no statistical significant differences between the average of the experimental and control groups for teaching sports exercises in the basic stage in Khartoum state in pre-test. There are statistically significant differences between the mean of the experimental group (active learning strategy) and the control group (the traditional method) for teaching physical exercise in the basic stage in Khartoum state in the post-test for experimental group.